A STUDY OF THE SOCIO-ECONOMIC AND CULTURAL ASPECTS OF THE MISING COMMUNITY AS REFLECTED IN RAJANIKANTA BORDOLOI`S MIRI JIYORI USING THE CONCEPT OF ASSAMOLOGY - Gogoi, Malaya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Concept of `Assamology` is a new concept. The popularisation of the concept can be credited to Maheshwar Neog. Assamology as a concept has been developed on the basis of concepts like Orientology and indology. The scope of the concept of `Assamology is very broad. The geographical, political, socio-economic and the cultural study of Assam and many other such areas of study can be included in Assamology.